Importance and Basic Steps of Training Soft Skills to Children in Globalized World – An Overview of The Matter In Vietnam - Thi Phuong Thao Huynh (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2018)
Soft Skills fulfill an important role in shaping an individual’s personality, and should be introduced in the very early stages of childhood. In a competitive globalized world, the value of these skills is further enhanced. Soft Skills, especially life skills, help them know how to cope with daily situations as well as on more long-term choices. If children are well-equipped with Soft Skills, they will have the flexibility to manage their lives when they grow up. The field research in this paper was used to obtain a deeper understanding of how soft skills influent to children’ future as well as an overview of Vietnam on the matter.